2017
DOI: 10.4330/wjc.v9.i9.761
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficiency and cost effectiveness of Bivalirudin: A systematic review

Abstract: AIMTo review the early and more recent studies of Bivalirudin, to assess the safety, effectiveness, and cost benefits of this drug.METHODSLiterature search of MEDLINE and PubMed databases from 1990 to 2017 using keywords as “bivalirubin” and “angiomax”, combined with the words “safety”, “effectiveness”, “efficiency”, “side effects”, “toxicity”, “adverse effect”, and “adverse drug reaction”.RESULTSA total of 66 publications were reviewed. The changes in clinical practice and differences in clinical protocols ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“… 38 To assess whether AC magnetic susceptibility can track the effect of these drugs in blood coagulation, measurements of the out-of-component signal of AC magnetic susceptibility were performed ex vivo in freshly donated human whole blood samples. Following guidelines of clinical doses for rivaroxaban 39 and bivalirudin, 40 IONPs-labelled blood samples were pre-treated with either 20, 100 and 200 ng mL −1 of rivaroxaban ( Fig. 5 ) or 2, 10 and 20 μg mL −1 of bivalirudin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 38 To assess whether AC magnetic susceptibility can track the effect of these drugs in blood coagulation, measurements of the out-of-component signal of AC magnetic susceptibility were performed ex vivo in freshly donated human whole blood samples. Following guidelines of clinical doses for rivaroxaban 39 and bivalirudin, 40 IONPs-labelled blood samples were pre-treated with either 20, 100 and 200 ng mL −1 of rivaroxaban ( Fig. 5 ) or 2, 10 and 20 μg mL −1 of bivalirudin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…such as use of femoral or radial access; the dose of heparin used; adjunct medication use such as prerandomization heparin use, unplanned versus planned GPI, and P2Y12 receptor inhibitor potency; and the use of dosing and duration of a bivalirudin post-PCI infusion. Even though numerous study-level systematic reviews and meta-analyses have been published, 4,12,13,49 none has clearly identified subgroups that may particularly benefit from a bivalirudinbased or a heparin-based regimen. Such studies are also unable to account for heterogeneity in endpoint measures, adjust for confounders, or examine the temporal relationships in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, one study illustrated that the use of bivalirudin in patients with STEMI who undergo primary PCI is cost-effective compared with the use of heparin (33). These controversial results may be due to the existence of some confounding factors (34). Taken together, the comparison of cost-effectiveness between bivalirudin and heparin is uncertain and required to be verified in further studies.…”
Section: A Univariate Logistic Regression Analysis 95% CImentioning
confidence: 99%